Pemanfaatan bungkil kelapa fermentasi dalam pada ikan nila (Oreochromis niloticus) - Horopu, Meyriska C.; Sampekalo, Julius; Lantu, Sartje (e-Journal BUDIDAYA PERAIRAN, 2018)
The purpose of this study was to determine the concentration of the use of the best fermented coconut pulp in feed on the growth of tilapia.  The research  used 12  nets  measuring 1x1 m placed in a concrete pond measuring 3.5 x 5 cm. The treatments were A (without fermented coconut pulp), B (10% fermented coconut pulp), C (20% fermented coconut pulp), and D (30% fermented coconut pulp). The experimental method used was a completely randomized design with 4 treatments and 3 repetitions. Data collected were absolute growth, daily growth, relative growth, and feed efficiency. The results of the variance analysis showed an influence in the growth of tilapia size 5-8 cm. The best growth and feed efficiency value occurred in treatment D Thus  the use of  30% fermented coconut pulp in fish food could improve the growth of tilapia.Key words : fermented coconut pulp, tilapia, growth feed efficiency